Biocatalysis: fungi mediated novel and selective 12 beta- or 17 beta-hydroxylation on the basic limonoid skeleton - Haldar, Saikat; Kolet, Swati P.; Thulasiram, Hirekodathakallu V. (Green Chemistry, 2013)
Basic limonoids carrying a 4,4,8-trimethyl-17-furanylsteroid skeleton are a class of triterpenoids and well-known for their insecticidal as well as a vast array of pharmacological activities. Rare and synthetically challenging 12 beta- and 17 beta-hydroxylation was achieved on the basic limonoid skeleton to produce a novel series of hydroxylated limonoids using fungi-mediated biocatalysis. The fungal system belonging to the genera of Mucor efficiently converted azadiradione, epoxyazadiradione, gedunin and their derivatives into corresponding 12 beta- and/or 17 beta-hydroxy derivatives. The position and stereochemistry of hydroxylation was determined by rigorous spectroscopic and crystallographic studies. This fungi-mediated stereo- and regio-selective hydroxylation process was highly efficient and mild enough to sustain chemically sensitive functional groups around the basic limonoid skeleton. Modifications of specific functional groups and variation in biocatalyst were shown to bring selectivity among 12 beta- or 17 beta-hydroxylation.

Biocatalyst mediated production of 6 beta,11 alpha-dihydroxy derivatives of 4-ene-3-one steroids - Kolet, Swati P.; Niloferjahan, Siddiqui; Haldar, Saikat; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (Steroids, 2013)
Biotransformation of steroids with 4-ene-3-one functionality such as progesterone (I), testosterone (II), 17 alpha-methyltestosterone (III), 4-androstene-3,17-dione (IV) and 19-nortestosterone (V) were studied by using a fungal system belonging to the genera of Mucor (M881). The fungal system efficiently and quantitatively converted these steroids in regio- and stereo-selective manner into corresponding 6 beta,11 alpha-dihydroxy compounds. Time course experiments suggested that the transformation was initiated by hydroxylation at 6 beta- or 11 alpha-(10 beta-hydroxy in case of V) to form monohydroxy derivatives which upon prolonged incubation were converted into corresponding 613,11oc-dihydroxy derivatives. The fermentation studies carried out using 5 L table-top fermentor with substrates (I and II) clearly indicates that 6 beta,11 alpha-dihydroxy derivatives of steroids with 4-ene-3-one functionality can be produced in large scale by using M881. (C) 2013 Elsevier Ltd.
Keywords: 4-Ene-3-one steroids; Biotransformation; Mucor sp.

Biocatalyst mediated functionalization of salannin, an insecticidal limonoid - Haldar, Saikat; Kolet, Swati P.; Dandekar, Devdutta S.; Kale, Balaji S.; Gonnade, Rajesh G.; Thulasiram, Hirekodathakallu V. (RSC Advances, 2014)
Transformation of salannin, an insecticidal C-seco limonoid was investigated using a fungal system, Cunninghamella echinulata. Salannin was efficiently converted into two metabolites, where the C-17 furan moiety was transformed into gamma-hydroxybutenolide (salanninolide) and N-(2-hydroxyethyl)-alpha,beta-unsaturated-gamma-lactam (salanninactam) analogues. Present studies have indicated salanninolide to be a metabolite in the C-seco limonoid biosynthetic pathway.